RELIGIOUS FACTOR COVARIATE ON SUBSTANCE ABUSE AMONG UNIVERSITY STUDENTS: A COMPARATIVEANALYSIS BETWEEN GENDER - Khaizir hj Ismail (AL-FIKRA, 2014)
This  research examines  the  issue   of  substance  abuse among first   year   students  of  National University of Malaysia. A total  of  1000 students  aged 18 until  23  years old comprising 271 male and   729 female  students   were  involved in  the  study.  To measure    the     level   of    tendency    to    abusedrugs,     SASSI-2(Substance  Abuse  Subtle  Screening), a psychology  measuring instrument   was    used,  containing 8  scales  which  are   Family friends    risk,    Attitude,   symptom,    Obvious  attributes,   subtle attributes,  Defensiveness,  Supplemental  addiction measure  dan Correctional. Meanwhile,  religiosity instrument  is  used   for   the purpose  of  measuring the  practice of  religious duties.   From the independent  sample t-test and  Multivariate Analysis  of  Variance (MANOVA) conducted,   differences   in   the   pattern   of substanceabuseamong      male    and     female     students     were identified.  The  result of  multivariate analisis covariate test (MANCOVA)showed  that  religiosity can  be  a determining factor in the tendency  of students  to be involved in substance  abuse